ASSESSMENT OF ANCHOR BORROWER PROGRAM AMONG MAIZE FARMERS IN KAURU LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA - Yusuf, A.; Danwanka, A. H.; Bose, A. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study assessed Anchor Borrower Program (ABP) among maize farmers in Kauru Local Government Area of Kaduna State, Nigeria. Multi-stage sampling techniques consisting purposive and random sampling was used in selection of 157 farmers for the study. Data were collected using structured questionnaire and analysed using both descriptive and inferential statistics. The results revealed that maize farmers were age range of 30-39 with an average age of 41 years. It also revealed that (74.2%) of the farmers were male. The result further shows that majority (73.5%) of the farmers were married with an average of 22 years of farming experience. The result further reveals that majority (87.4%) of the farmers took farming as a major occupation. It also showed that 34.4% maize farmers had attended tertiary education as their level of education. Majority (89.56%) of the farmers acquired their land through inheritance, while majority (64.9%) of the farmers had farm size of 2.5 to 4 hectares with an average farm size of 2.5 hectares. Result further shows that 31.4% of the farmers acquired their loan through uptakers and 29.6% of them acquired their input through Bank of Agriculture. The results also revealed that majority (87.4%) of maize farmers had increase in income after using the loan. The results of regression analysis revealed that R2 was 0.365 meaning that 36.5% of the variation in the dependent variable was explained by the independent or explanatory variables included in the model. The coefficient of age and marital status has a negative and significant at a P<0.01 level of probability, farm size and land tenure had a positive coefficient and highly significant at P<0.01. The major constraints affecting farmers in anchor borrower programme were fluctuating of price, cumbersome process or stringent process, distance from financial institution, high Family expenditure and low productivity due to harsh weather condition. The study concluded that ABP enhanced the output and income of maize farmers in study area. Based on the finding, it is recommended that, all stringent conditions attached to access to loan for agricultural production should be removed, ABP facilitators should ensure timely disbursement of funds and input before planting commences.